Pelindungan Hukum Ekspresi Budaya Tradisional Terhadap Alat Musik Kulcapi Sebagai Warisan Budaya Takbenda Masyarakat Karo Menurut Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Sinurat, Bima Pandawa; Ginting, Dana Diva Ivan De La Pena; Damanik, Innes Ferancia; Sembiring, Otista C A (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyzethe legal protection of kulcapi as a form of traditional cultural expressionof the Karo people, based on Law Number 28 of 2014 concerning Copyright, as well as evaluating the role of the government in efforts to preserve it.Kulcapi, as a form of intangible cultural heritage, has important historical andcultural value, but its legal protection is still only normativeand has not been properly implemented at the regional level. The methodused in this study is an empirical juridical approach bygathering information from literature studies and interviews withkulcapi artists in Lingga Cultural Village. The results of the study show that although the Copyright Law provides a legal basis for protecting traditional cultural expressions,the local government has not carried out the data collection, documentation, or coaching programsnecessary to maintain the sustainability of kulcapi. In addition, social changes and declining interest among the younger generation also posechallenges in efforts to preserve this traditional musical instrument. This studyconcludes that in order to protect the kulcapi, i cooperation betweenlegal regulations, an active role by the local government, and cultural regeneration efforts are neededso that the kulcapi remains part of the Karo community's identity.